'I hate Beyoncé and I don't care who knows it': Towards an ethics of studying anti-fandom. (1st September 2016) - Jones, Bethan
The field of audience studies has undergone something of a change in the last twenty years. From considering film and television viewers to be passive consumers, scholars now recognize the active role that audiences play in the construction and reception of texts. Similarly, understandings of the need to look beyond the fan to the non-fan and anti-fan have also changed the ways we view the text and its audiences. This work has been fuelled, at least in part, by the development of fan studies, with academics like Henry Jenkins, Matt Hills and Jonathan Gray arguing that fans actively work with a text to change its meaning, or uncover hidden meanings, through fan cultural production. The emergence of Web 2.0 has further changed the nature of audience interaction, with fannish activities like fan fiction no longer the preserve of paper 'zines. The growth of social media sites along with the shifting interest in analysing fans and their engagement with texts raises complex ethical questions about how scholars negotiate the study of fandom, but the ethics of how we engage with anti-fans and analyse anti-fannish response to a text has thus far been ignored. Fan studies, as a relatively new area of scholarship, has traditionally adopted two different means of dealing with fans. The first, drawing on the literary studies tradition, prioritizes the text. In this mode, texts are properly cited to ensure that others can find them and it may not occur to scholars to not point to the source. The second, however, arises from the social sciences in which human subjects are worked with and ethical considerations come above and beyond the research. In this mode, fans' privacy is respected and permission obtained in order to cite fannish works. In this article I examine the ethics of approaching anti-fans. Is it enough to approach them in the same way as we approach fans or are there other factors to consider? Is it appropriate to use anti-fan texts without the authors' consent? Where do the power structures lie in analysing anti-fans as opposed to fans? And should fan studies scholars even be asking for consent from anti-fans in an increasingly open media space?